2022
DOI: 10.52547/edcj.15.47.27
|View full text |Cite
|
Sign up to set email alerts
|

Clinical self-efficacy of final-year nursing students: A comparison of a 360-degree evaluation method with a conventional method

Abstract: Background & Objective: The use of traditional clinical evaluation methods is one of the most critical challenges in obtaining professional competence and self-efficacy in clinical performance. This study aims to investigate the clinical self-efficacy of final-year nursing students by comparing a 360-degree evaluation method with a conventional evaluation method.Materials & Methods: This quasi-experimental study was conducted on 65 final-year nursing students at Abhar School of Nursing who were selected by cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Inconsistent with these results, the findings of some studies have indicated that students had a high level of self-efficacy [ 17 , 35 , 36 ], although Zhang et al reported the level of self-efficacy of Chinese students as low [ 37 ]. Considering the many factors affecting the self-efficacy of nursing students such as academic semester, type of education and clinical training, achieving different results of self-efficacy levels in different studies is predictable and inevitable [ 17 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent with these results, the findings of some studies have indicated that students had a high level of self-efficacy [ 17 , 35 , 36 ], although Zhang et al reported the level of self-efficacy of Chinese students as low [ 37 ]. Considering the many factors affecting the self-efficacy of nursing students such as academic semester, type of education and clinical training, achieving different results of self-efficacy levels in different studies is predictable and inevitable [ 17 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%